Photobiomodulation Promotes Hippocampal CA1 NSC Differentiation Toward Neurons and Facilitates Cognitive Function Recovery Involving NLRP3 Inflammasome Mitigation Following Global Cerebral Ischemia - Guo, Sihan; Wang, Ruimin; Hu, Jiewei; Sun, Liping; Zhao, Xinru; Zhao, Yufeng; Han, Dong; Hu, Shuqun (Frontiers in Cellular Neuroscience, 2021)
Our recent study revealed that photobiomodulation (PBM) inhibits delayed neuronal death by preserving mitochondrial dynamics and function following global cerebral ischemia (GCI). In the current study, we clarified whether PBM exerts effective roles in endogenous neurogenesis and long-lasting neurological recovery after GCI. Adult male rats were treated with 808 nm PBM at 20 mW/cm2 irradiance for 2 min on cerebral cortex surface (irradiance ~7.0 mW/cm2, fluence ~0.8 J/cm2 on the hippocampus) beginning 3 d after GCI for five consecutive days. Cognitive function was evaluated using the Morris water maze. Neural stem cell (NSC) proliferation, immature neurons, and mature neurons were examined using bromodeoxyuridine (BrdU)-, doublecortin (DCX)-, and NeuN-staining, respectively. Protein expression, such as NLRP3, cleaved IL1β, GFAP, and Iba1 was detected using immunofluorescence staining, and ultrastructure of astrocyte and microglia was observed by transmission electron microscopy. The results revealed that PMB exerted a markedly neuroprotective role and improved spatial learning and memory ability at 58 d of ischemia/reperfusion (I/R) but not at 7 d of reperfusion. Mechanistic studies revealed that PBM suppressed reactive astrocytes and maintained astrocyte regeneration at 7 d of reperfusion, as well as elevated neurogenesis at 58 d of reperfusion, as evidenced by a significant decrease in the fluorescence intensity of GFAP (astrocyte marker) but unchanged the number of BrdU-GFAP colabeled cells at the early timepoint, and a robust elevation in the number of DCX-NeuN colabeled cells at the later timepoint in the PBM-treated group compared to the GCI group. Notably, PBM treatment protected the ultrastructure of astrocyte and microglia cells at 58 d but not 7 d of reperfusion in the hippocampal CA1 region. Furthermore, PBM treatment significantly attenuated the GCI-induced immunofluorescence intensity of NLRP3 (an inflammasome component), cleaved IL1β (reflecting inflammasome activation) and Iba1, as well as the colocalization of NLRP3/GFAP or cleaved IL-1β/GFAP, especially in animals subjected to I/R at 58 d. Taken together, PBM treatment performed postischemia exerted a long-lasting protective effect on astrocytes and promoted endogenous neurogenesis in the hippocampal CA1 region, which might contribute to neurological recovery after GCI.